El periodismo en Rumanía desde sus inicios (1790) hasta el primer tercio del siglo xx (1927) - Vorneanu, Valeriu; Enachi, Larisa; Sagredo, Félix (Documentación de las Ciencias de la Información, 2007)
This work represents a run lengthways from the appearance of the journalism in Rumania until the XXth century in the periods of the revolutionary censure, relieving the working environment of the famous writers of that period. Showing that the journalism was the main tool in the social, political and cultural lives, emphasizing the created environment of that period. This work exposes the statistics dates about the variety of languages in which were publishing for the minorities, in some regions being influenced by the bolchevique propaganda, with the purpose to serve the same, also commenting the importance in appearance of the press associations which were having as activity to assure the distribution of helps and the judicial assistance.